THE EFFECT OF TRAINING AND DEVELOPMENT, ORGANIZATIONAL CULTURE, AND CAREER GROWTH ON EMPLOYEE PRODUCTIVITY IN STATE-OWNED ENTERPRISES - Melawati, Fitri (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study examines the influence of training and development, organizational culture, and career growth on employee productivity in State-Owned Enterprises (SOEs). Using a quantitative approach, data were collected from employees of SOEs and analyzed using Structural Equation Modeling (SEM-PLS). The findings reveal that all three factors significantly contribute to employee productivity, with career growth having the strongest effect, followed by training and development and organizational culture. These results highlight the critical role of career advancement opportunities in enhancing employee motivation and performance. The study supports the Resource-Based View (RBV) theory, emphasizing the strategic importance of human capital investment. Additionally, the findings align with the Job Characteristics Model and Self-Determination Theory, indicating that employees are more productive when provided with meaningful work, skill development, and career progression opportunities. Based on these findings, it is recommended that SOEs prioritize career development programs, implement continuous training initiatives, and foster a positive organizational culture to maximize productivity. Future research could explore additional factors such as work-life balance, leadership styles, and digital transformation to further understand productivity dynamics in SOEs.